The Moonstone - Wilkie Collins 1824-1889; Anthea Beamish (UK Longmans, Green and Co., 1961)
Wilkie Collins's "The Moonstone" is generally considered the first full length detective novel in the English language. The Moonstone, a large and valuable, yellow diamond, plundered from an Indian temple by Colonel Herncastle during the Siege of Seringapatam, is rumored to bring bad luck to its owner. The Colonel bequeathes the diamond to his niece Rachel Verinder on her eighteenth birthday. At her birthday party, Rachel wears the Moonstone for all to see, later that night the priceless stone is stolen again and an investigation ensues to discover the identity of the thief and recover the jewel. When Sergeant Cuff is brought in to investigate the crime, he soon realizes that no one in Rachel's household is above suspicion. Hailed by T. S. Eliot as "the first, the longest, and the best of modern English detective novels," and described by G. K. Chesterton as "probably the best detective tale in the world," "The Moonstone" is one of Wilkie Collins's most popular works which influenced the development of an entirely new genre of fiction. The Moonstone is a marvellously taut and intricate tale of mystery, in which facts and memory can prove treacherous and not everyone is as they first appear.
Edited and Abridged
Keywords: Literature (3GdCOHs; General -- Fiction; Jewelry theft; Police -- England -- Fiction; East Indians -- England -- Fiction; Moonstones -- Fiction